NEUROPROTECTIVE EVALUATION OF LAGENARIA VULGARIS EXTRACT HYPOXIC NEUROTOXICITY INDUCED RATS - Adnaik, Rahul Shivaji; Krishna Mohite, Shrinivas (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: The present study was aimed to evaluate the neuroprotective effects of Lagenaria vulgaris seed oil (LVSO) in hypoxic neurotoxicity induced neurodegeneration in mice. Methods: Hypoxia was induced by providing sodium nitrite (5 ml/kg) in drinking water to mice for 14 days and mice were evaluated for elevated plus maze test. On 15th day, mice were sacrificed and brain was isolated for estimation of non-enzymatic antioxidants (glutathione [GSH]), enzymatic antioxidants superoxide dismutase (SOD), catalase (CAT), total protein (TP) in the brain tissue, and histopathological study. Results: Treatment with LVSO significantly prevented raise in levels of oxidant enzymes. CAT, GSH, SOD, and TP content have significantly restored in LVSO treated groups whereas toxic group has shown a significant decrease in levels compare to control group. LVSO (0.5 mg/kg) has shown maximum protection. The observed results leading to neurodegeneration is also confirmed by the histopathological differences between treatment and hypoxic mice Conclusion: LVSO ameliorated antihypoxic effects induced by sodium nitrite and this effect may be mediated by antioxidant mechanism, thereby enhancing neuroprotection. Keywords: Neuroprotective, Antioxidants, Hypoxia, Seed oil.